2021
DOI: 10.3904/kjim.2019.040
|View full text |Cite
|
Sign up to set email alerts
|

Sex difference in bowel preparation quality and colonoscopy time

Abstract: Background/Aims: The length of colon is known to be longer in females than in males. In addition, the morphology of colon cancer is different between males and females. The aim of this study was to investigate sex differences in Boston bowel preparation score (BBPS) and colonoscopy insertion time. Methods: This study retrospectively analyzed medical records and colonoscopy readings of subjects who underwent colonoscopy at Seoul National University Bundang Hospital from March 2015 to April 2018. BPPS was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…11,13,[19][20][21][22] The difference in cecal insertion time between males and females might originate from anatomical differences. Compared with males, females have a longer colon, less visceral fat and abdominal muscle to support the colon, and a deeper pelvis, 13,[23][24][25] all of which predispose to loop formation during colonoscopy. 13,[23][24][25] Patients with lower BMI have less visceral fat to support the colon to prevent looping and a smaller abdominal cavity and thus more acute bends of the colon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,13,[19][20][21][22] The difference in cecal insertion time between males and females might originate from anatomical differences. Compared with males, females have a longer colon, less visceral fat and abdominal muscle to support the colon, and a deeper pelvis, 13,[23][24][25] all of which predispose to loop formation during colonoscopy. 13,[23][24][25] Patients with lower BMI have less visceral fat to support the colon to prevent looping and a smaller abdominal cavity and thus more acute bends of the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with males, females have a longer colon, less visceral fat and abdominal muscle to support the colon, and a deeper pelvis, 13,[23][24][25] all of which predispose to loop formation during colonoscopy. 13,[23][24][25] Patients with lower BMI have less visceral fat to support the colon to prevent looping and a smaller abdominal cavity and thus more acute bends of the colon. 20,26 A history of constipation and less experienced endoscopist were also associated with longer insertion times in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Age, sex, physical activity, socioeconomic status, educational level, and comorbidity may significantly affect colonoscopy quality 1,60,61 . Predictors of poor BP include age (odds ratio [OR] = 1.14), tobacco use (OR = 1.28), narcotic use (OR = 1.28), hypertension (OR = 1.25), diabetes mellitus (OR = 1.38), obesity (OR = 1.46), low education (OR = 1.49), dementia (OR = 2.09), and calcium‐channel blockers (OR = 3.2), as reported in different reviews and meta‐analyses 61–64 . Hospitalization is another independent predictor of poor BP 65 .…”
Section: Patient Factorsmentioning
confidence: 99%
“… 1 , 60 , 61 Predictors of poor BP include age (odds ratio [OR] = 1.14), tobacco use (OR = 1.28), narcotic use (OR = 1.28), hypertension (OR = 1.25), diabetes mellitus (OR = 1.38), obesity (OR = 1.46), low education (OR = 1.49), dementia (OR = 2.09), and calcium‐channel blockers (OR = 3.2), as reported in different reviews and meta‐analyses. 61 , 62 , 63 , 64 Hospitalization is another independent predictor of poor BP. 65 A recent Italian multicenter study developed and validated a model to identify hospitalized patients with inadequate bowel cleansing.…”
Section: Patient Factorsmentioning
confidence: 99%
“…Previous studies have found that age, sex, physical activity, daily bowel movements, being examined in the afternoon, the time between finishing bowel preparation and examination, split dose and different education methods were associated with bowel preparation quality. [ 2 , 5 ] Although education and timing of bowel preparation were influential,[ 2 ] there is no clear consensus on the relative importance of these factors. A national CRC screening programme in China, initiated in 2018, provided data for secondary analysis to explore the factors which could improve bowel preparation quality before colonoscopy.…”
Section: Introductionmentioning
confidence: 99%